pK(a)-Directed host-guest assemblies: rational analysis of molecular adducts of 2,4-diamino-6-methyl-1,3,5-triazine with various aliphatic dicarboxylic acids - Delori, Amit; Suresh, Eringathodi; Pedireddi, V. R. (Chemistry-A European Journal, 2008)
Molecular adducts of 2,4-diamino-6-methyl-1,3,5-triazine (1) have been prepared with various aliphatic dicarboxylic acids. The molecular complexes (1a-1i) thus formed by co-crystallizing 1 with oxalic, malonic, succinic, fumaric, acetylene dicarboxylic, glutaric, thiodiglycolic, diglycolic, and adipic acids have been found to give two types of host-guest assemblies that have voids or channels in a three-dimensional arrangement. The different types of host-guest arrangement appear to result from differences in the acidity of the dicarboxylic acids, that is, acids with pK(a) < 3.0 give host networks that consist of 1 and the corresponding acid with water or solvent molecules of crystallization present as guests, whereas acids with pK(a) > 3.0 exist as guests in voids in a host network formed by 1. The former arrangement is observed in adducts 1a, 1b, 1c, and 1h and the latter arrangement is found in adducts 1c, 1d, 1f, 1g and 1i.
Keywords: dicarboxylic acids; host-guest systems; hydrogen bonds; molecular recognition; supramolecular chemistry

Receptor design and extraction of inorganic fluoride ion from aqueous medium - Das, Priyadip; Mandal, Amal Kumar; Kesharwani, Manoj K.; Suresh, Eringathodi; Ganguly, Bishwajit; Das, Amitava (Chemical Communications, 2011)
A receptor with acidic methylene hydrogens is found to act as an efficient binding mode for F−. This reagent could as well be used for selective and quantitative extraction of F− from the aqueous solution of NaF and sea water.

Alternative approach: a highly selective dual responding fluoride sensor having active methylene group as binding site - Das, Priyadip; Kesharwani, Manoj K.; Mandal, Amal K.; Suresh, Eringathodi; Ganguly, Bishwajit; Das, Amitava (Org Biomol Chem., 2012)
A newly designed phosphonium derivative (L) having active methylene functionality, shows unusual preference towards F− over all other anions. The binding process through C–H⋯F− hydrogen bond formation was probed by monitoring the changes in either electronic or luminescence spectra. Changes in both cases are significant enough to allow visual detection. The loss of molecular flexibility of L on forming L·F− effectively interrupts the non-radiative deactivation pathway and accounts for the observed switch on fluorescence response. The results of the time-resolved emission studies for L and L·F− using a time-correlated single photon counting technique further corroborate this presumption. The excellent preference of L towards F− is attributed to an efficient hydrogen bonding interaction between the strongly polarized methylene protons and F−, which delineates the subtle difference in the affinity among other competing anionic analytes like CN−, H2PO4−, CH3CO2−, etc. The relative affinities of various anions and the preferential binding of F− to reagent L are also rationalized using computational studies.

Tandem [4 + 2]/[2 + 2] cycloaddition reactions involving indene or benzofurans and arynes - Bhojgude, Sachin Suresh; Thangaraj, Manikandan; Suresh, Eringathodi; Biju, Akkattu T. (Organic Letters, 2014)
The reaction of arynes with indene/benzofurans has been developed. The arynes were generated from 2-(trimethylsilyl)aryl triflates by the fluoride-induced 1,2-elimination react with indene or various benzofurans proceeding via a cascade reaction involving the Diels–Alder reaction and a [2 + 2] cycloaddition reaction. The tandem process afforded functionalized dihydrobenzocyclobutaphenanthrenes in moderate to good yields. Moreover, the method has been utilized for the one-pot synthesis of benzo[b]fluoranthene.

Enantioselective synthesis of functionalized pyrazoles by NHC-catalyzed reaction of pyrazolones with alpha,beta-unsaturated aldehydes - Yetra, Santhivardhana Reddy; Mondal, Santigopal; Suresh, Eringathodi; Biju, Akkattu T. (Organic Letters, 2015)
The N-heterocyclic carbene (NHC)-organocatalyzed enantioselective annulation reaction of pyrazolones with alpha,beta-unsaturated aldehydes proceeding via the chiral alpha,beta-unsaturated acyl azolium intermediates under oxidative conditions is presented. The reaction afforded dihydropyranone-fused pyrazoles in moderate to good yields and good er values under operationally simple and base-free conditions.